Association of Attention-Deficit/Hyperactivity Disorder Diagnosis With Adolescent Quality of Life - Kazda, Luise; McGeechan, Kevin; Bell, Katy; Thomas, Rae; Barratt, Alexandra (My University, 2022)
Appropriate diagnosis of attention-deficit/hyperactivity disorder (ADHD) can improve some short-term outcomes in children and adolescents, but little is known about the association of a diagnosis with their quality of life (QOL). To compare QOL in adolescents with and without an ADHD diagnosis. This cohort study followed an emulated target trial design using prospective, observational data from the Longitudinal Study of Australian Children, a representative, population-based prospective cohort study with biennial data collection from 2006 to 2018 with 8 years of follow-up (ages 6-7 to 14-15 years). Propensity score matching was used to ensure children with and without ADHD diagnosis were well matched on a wide range of variables, including hyperactive/inattentive (H/I) behaviors. Eligible children were born in 1999 to 2000 or 2003 to 2004 and did not have a previous ADHD diagnosis. All incident ADHD cases were matched with controls. Data were analyzed from July 2021 to January 2022. Incident parent-reported ADHD diagnosis at age 6 to 7, 8 to 9, 10 to 11, 12 to 13, or 14 to 15. Quality of life at age 14 to 15 was measured with Child Health Utility 9D (CHU9D) and 8 other prespecified, self-reported measures mapped to the World Health Organization's QOL domains. Pooled regression models were fitted for each outcome, with 95% CIs and P values calculated using bootstrapping to account for matching and repeat observations. Of 8643 eligible children, a total of 393 adolescents had an ADHD diagnosis (284 [72.2%] boys; mean [SD] age, 10.03 [0.30] years; mean [SD] H/I Strengths and Difficulties Questionnaire score, 5.05 [2.29]) and were age-, sex-, and H/I score-matched with 393 adolescents without ADHD diagnosis at time zero. Compared with adolescents without diagnosis, those with an ADHD diagnosis reported similar QOL on CHU9D (mean difference, -0.03; 95% CI, -0.07 to 0.01; P = .10), general health (mean difference, 0.11; 95% CI, -0.04 to 0.27; P = .15), happiness (mean difference, -0.18; 95% CI, -0.37 to 0.00; P = .05), and peer trust (mean difference, 0.65; 95% CI, 0.00 to 1.30; P = .05). Diagnosed adolescents had worse psychological sense of school membership (mean difference, -2.58; 95% CI, -1.13 to -4.06; P < .001), academic self-concept (mean difference, -0.14; 95% CI, -0.02 to -0.26; P = .02), and self-efficacy (mean difference, -0.20; 95% CI, -0.05 to -0.33; P = .007); displayed more negative social behaviors (mean difference, 1.56; 95% CI, 0.55 to 2.66; P = .002); and were more likely to harm themselves (odds ratio, 2.53; 95% CI, 1.49 to 4.37; P < .001) than adolescents without diagnosis. In this cohort study, ADHD diagnosis was not associated with any self-reported improvements in adolescents' QOL compared with adolescents with similar levels of H/I behaviors but no ADHD diagnosis. ADHD diagnosis was associated with worse scores in some outcomes, including significantly increased risk of self-harm. A large, randomized clinical trial with long-term follow-up is needed.
JAMA Network Open
Keywords: Adolescents and youth; Health and wellbeing